The metaphor of the dog in Arabic Literature - Yasien Mohamed (Tydskrif vir Letterkunde, 2018)
This essay deals with the metaphor of the dog in Arabic philosophical literature. The metaphor is viewed in relation to the imagery of the rider and the horse, which vividly demonstrates the dynamic relation of the three faculties of the soul. Our focus is on the irascible faculty, the emotion of anger. The dog metaphor brings out the positive dimension of emotion. Classical Arabic literature views the soul as a substance distinct from the body, and has many illustrations showing the superiority of the soul over the body. What makes the soul special is its rational faculty, its capacity to reason. In the rider-horse imagery, the rider is the metaphor for reason, the horse the metaphor for passion, and the dog the metaphor for anger. A balanced soul coordinates these faculties in right proportion. The imagery of horse-riding, used in Arabic and Greek philosophical literature, provides the most powerful image to explain how the three faculties of the soul interact with one another. The article examines the imagery from a literary and philosophical perspective. Scientific knowledge of the horse and dog will enhance our insight and appreciation of the richness of the metaphor. The method of analysis is based on four primary classical texts: Aristotle’s Nichomachean Ethics in Miskawayh’s eleven century Arabic translation, Tahdhib al-Akhlaq (Refinement of Character ), Galen’s Ethics in Arabic translation, and al-Raghib al-Isfahani’s al-Dhari’ah ila Makarim al-Shari’ah (“The Means to the Noble Qualities of the Law”).